Modulation of the turkey β1-adrenergic receptor by membrane rafts: insight from molecular dynamics - Ghumman, Afshan; Robinson, David (Wiley, 2016)
G-protein coupled receptors are targets for ~70% of drugs. These receptors are responsible for signal transduction within a cell membrane (and further into the cell) and disruption to this signaling cascade is responsible for several non-infectious diseases. Membrane rafts exhibit significantly altered properties in comparison to fluid bilayers and as such may regulate certain GPCR’s, or be responsible for errors in signaling. Using molecular dynamics, we have investigated the conformations of the turkey β1-adrenergic receptor with and without an agonist in sphingolipid and cholesterol rich bilayers, typical of raft compositions, and compared these to cholesterol-poor bilayers. We find that the raft-like lipid bilayers are responsible for significantly altering the conformation of the receptor, even when an agonist is present.